Rancangan Trainer Penerapan Rangkaian Elektronika Kelas XI Kompetensi Keahlian Teknik Audio Video SMKN 5 Jakarta (PENDIDIKAN VOKASIONAL TEKNIK ELEKTRONIKA FAKULTAS TEKNIK UNIVERSITAS NEGERI JAKARTA, 2021)
The research aims to implement Learning Media in the form of a Subject Trainer for the Electronics Circuits of Application in Class XI Audio Video Engineering expertise competence in Vocational High School of 5 Jakarta, and test the level of eligibility based on assessment from material experts and media experts. This study uses research and development methods (Research and Development) which include: 1)potential problems, 2)data collection, 3)product design, 4) design validation, 5)design revisison, 6)product testing, 7)product revision, 8) trial usage,9) media ready to use. The results of the learning media design of the Electronics Circuit Trainer Application are used for practicum on FET / MOSFET material as power amplifier, MOSFET as Switch, Sensor with Temperature and Light Transducer, Operational Amplifier (OP-AMP) and Frequency Filter. The results of the study are instructional media trainers who have been tested for eligibility as learning media. Based on the results of the feasibility test by material experts obtained an assessment percentage of 84.8%, media experts by 97.5% and for testing the use by students of Class XI Audio Video Engineering obtained an assessment of 88.05%. Based on the eligibility category, it can be concluded that the practicum trainer for the Electronics Circuits Application is very feasible.